The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12663-015-0850-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Oral and Maxillofacial Surgical Notes in an Indian Public Sector Hospital in Accordance with the Royal College of Surgeons Guidelines: A Completed Audit Loop Study

Abstract: Aim Proper and adequate documentation in operation notes is a basic tool of clinical practice with medical and legal implications. An audit was done to ascertain if oral and maxillofacial surgery operative notes in an Indian public sector hospital adhered to the guidelines published by the Royal College of Surgeons England. Methods Fifty randomly selected operative notes were evaluated against the guidelines by RCS England with regards to the essential generic components of an operation note. Additional criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Parameters such as operative diagnosis, complications, details of additional procedures, specifics of tissue manipulation, prosthesis identification, closure technique details, anticipated blood loss, and antibiotic and thromboembolism prophylaxis achieved compliance rates of 85%, 98%, 88%, 79%, 37%, 99%, 92%, 96%, and 98%, respectively. Our study findings align with similar investigations [ 3 , 12 - 14 ] where the implementation of a revised surgical pro forma led to a substantial increase in adherence to RCS guidelines.…”
Section: Discussionsupporting
confidence: 92%
“…Parameters such as operative diagnosis, complications, details of additional procedures, specifics of tissue manipulation, prosthesis identification, closure technique details, anticipated blood loss, and antibiotic and thromboembolism prophylaxis achieved compliance rates of 85%, 98%, 88%, 79%, 37%, 99%, 92%, 96%, and 98%, respectively. Our study findings align with similar investigations [ 3 , 12 - 14 ] where the implementation of a revised surgical pro forma led to a substantial increase in adherence to RCS guidelines.…”
Section: Discussionsupporting
confidence: 92%
“…14 Studies show that formalized teaching programs to introduce a new synoptic proforma, such as the RCS standards, have significantly improved documentation across surgical specialities. [16][17][18][19][20][21][22][23][24][25][26] However, writing a complete operation report with a checklist prompt does not always infer the acquisition of these skills or the trainee's understanding of the surgery. 1 Gur et al explored the educational value of synoptic report writing and concluded that using a proforma specifically highlights to trainees the essential steps of an operation and, if wellconstructed, can improve trainee familiarity with the patient's preand intra-operative findings.…”
Section: Discussionmentioning
confidence: 99%
“…From prior studies, the importance of complete operation documentation is undervalued in surgical training, 11,14,15 and 34% of responding Surgical Program Directors in The United States of America perceive formal education in operation report writing is not required 14 . Studies show that formalized teaching programs to introduce a new synoptic proforma, such as the RCS standards, have significantly improved documentation across surgical specialities 16–26 . However, writing a complete operation report with a checklist prompt does not always infer the acquisition of these skills or the trainee's understanding of the surgery 1 .…”
Section: Discussionmentioning
confidence: 99%
“…This documentation is an extremely important step for rehabilitation, allowing clinical evaluation of treatments, 1,2 for educational purposes, 3 research, comparison of treatment centers, 4 and legal records. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…This documentation is an extremely important step for rehabilitation, allowing clinical evaluation of treatments, 1,2 for educational purposes, 3 research, comparison of treatment centers, 4 and legal records. 5,6 In the rehabilitation protocol of the Hospital of Rehabilitation of Craniofacial Anomalies/USP (HRAC/USP), impression of dental arches is obtained at about before lip repair-3 months, before palate repair-12 months and 1 year after primary surgeries. 7 However, in practice, commercial trays do not possess correct size and shape to be used in dental arches of infants with cleft lip and palate, precluding the proper impression of these patients, because the tray size is bigger than the children's maxilla.…”
Section: Introductionmentioning
confidence: 99%